2021
DOI: 10.21203/rs.3.rs-712062/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence, Aetiology and Clinical Features of Eosinophilic Pleural Effusion: A Retrospective Study

Abstract: Background: Eosinophilic pleural effusion (EPE) is a distinct entity among pleural effusions, but its diagnostic and prognostic significance is still controversial. This study aimed to evaluate the incidence and aetiological distribution of EPE in our institution and to assess the relationship between EPE and malignancy and other underlying diseases and the relevance of the percentage of eosinophils and other laboratory parameters. Methods: A retrospective study was conducted by reviewing the medical records … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…In our study, many patients with autoimmune diseases showed eosinophil elevation in their pleural effusions. Eosinophilic pleural effusion, defined as a pleural effusion of at least 10% eosinophils within a white cell differential count, is commonly caused by trauma, infectious diseases, malignant tumours, and several medications, and autoimmune diseases with eosinophilic pleural effusion are rare [30][31][32]. Only four patients with autoimmune diseases in our study showed pleural fluid with eosinophil counts of ≥ 10%.…”
Section: Discussionmentioning
confidence: 62%
“…In our study, many patients with autoimmune diseases showed eosinophil elevation in their pleural effusions. Eosinophilic pleural effusion, defined as a pleural effusion of at least 10% eosinophils within a white cell differential count, is commonly caused by trauma, infectious diseases, malignant tumours, and several medications, and autoimmune diseases with eosinophilic pleural effusion are rare [30][31][32]. Only four patients with autoimmune diseases in our study showed pleural fluid with eosinophil counts of ≥ 10%.…”
Section: Discussionmentioning
confidence: 62%